Vulnerability Analysis of Power Grids Using Modified Centrality Measures. (3rd April 2013) - Gutierrez, Francisco; Barocio, E.; Uribe, F.; Zuniga, P.
Abstract : The aim of this paper is to propose modified centrality measures as a tool to identify critical nodes before a vulnerability analysis is performed in an electrical power grid. Pair dependency centrality is weighted using the grid active power flow, and this becomes the basis to define closeness and betweenness of its nodes, and hence to identify the most critical ones. To support the idea of using modified centralities, four power grids are tested to be either exponential or scale-free. To evaluate the proposal, information obtained via modified centrality measures is used to calculate global efficiency of the power grids.